Advances in Italian Mechanism Science Proceedings of the 3rd International Conference of IFToMM Italy - Niola, Vincenzo; Gasparetto, Alessandro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This book presents the proceedings of the 3rd International Conference of IFToMM ITALY, held online on September 9-11, 2020. It includes peer-reviewed papers on the latest advances in mechanism and machine science, discussing topics such as biomechanical engineering, computational kinematics, the history of mechanism and machine science, gearing and transmissions, multi-body dynamics, robotics and mechatronics, the dynamics of machinery, tribology, vibrations, rotor dynamics and vehicle dynamics. A valuable, up-to-date resource, it offers an essential overview of the subject for scientists and practitioners alike, and will inspire further investigations and research. .
Keywords: Robotics; Automation; Machinery; Manufactures; Robotics and Automation; Machinery and Machine Elements; Manufacturing, Machines, Tools, Processes